2010
DOI: 10.1073/pnas.1001725107
|View full text |Cite
|
Sign up to set email alerts
|

Repression of tyrosine hydroxylase is responsible for the sex-linked chocolate mutation of the silkworm, Bombyx mori

Abstract: Pigmentation patterning has long interested biologists, integrating topics in ecology, development, genetics, and physiology. Wild-type neonatal larvae of the silkworm, Bombyx mori , are completely black. By contrast, the epidermis and head of larvae of the homozygous recessive sex-linked chocolate ( sch ) mutant are reddish brown. When incubated at 30 °C, mutants with the sch allele fail to hatch; moreover, homozygous mutants carrying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
83
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 43 publications
11
83
0
1
Order By: Relevance
“…Of these, pale, yellow, and Ddc are previously known as melanin-promoting factors. CRISPR-induced knockouts in these three genes produced melanin repression phenotypes in accordance with expectations from Drosophila (Morgan 1916;Wright et al 1976a;True et al 1999;Wittkopp et al 2002b) and other insects including P. xuthus (Futahashi and Fujiwara 2005), Manduca sexta (Gorman et al 2007), Bombyx mori (Futahashi et al 2008;Liu et al 2010), Tribolium castaneum (Gorman and Arakane 2010), and Oncopeltus fasciatus (Liu et al 2016). Our findings support the idea that pale, yellow, and Ddc play deeply conserved roles in insect melanin pigmentation.…”
Section: Discussionsupporting
confidence: 78%
“…Of these, pale, yellow, and Ddc are previously known as melanin-promoting factors. CRISPR-induced knockouts in these three genes produced melanin repression phenotypes in accordance with expectations from Drosophila (Morgan 1916;Wright et al 1976a;True et al 1999;Wittkopp et al 2002b) and other insects including P. xuthus (Futahashi and Fujiwara 2005), Manduca sexta (Gorman et al 2007), Bombyx mori (Futahashi et al 2008;Liu et al 2010), Tribolium castaneum (Gorman and Arakane 2010), and Oncopeltus fasciatus (Liu et al 2016). Our findings support the idea that pale, yellow, and Ddc play deeply conserved roles in insect melanin pigmentation.…”
Section: Discussionsupporting
confidence: 78%
“…The only known tyrosinase-like enzymes in B. mori plasma are PPO1/PO1 and PPO2/PO2. However, the B. mori genome does encode a Tyr hydroxylase previously implicated in cuticle pigmentation (42) and whose ortholog in M. sexta is expressed in hemocytes (43). Three lines of evidence, however, argue against Tyr hydroxylase playing a role in the rapid melanization of B. mori plasma.…”
Section: B Mori Ppo Is Rapidly Processed After Collection From a Woundmentioning
confidence: 96%
“…Molecular genetic studies have identified the genes responsible for several colour pattern mutants in the silkworm [27][28][29] . Turner 30 introduced four different mutations of this silkworm, Moricaud (p M ), Zebra (Ze), Multilunar (L) and quail (q), which are good models for investigating caterpillar mimicry with various patterns.…”
mentioning
confidence: 99%